The recurrent p.Glu3Lys variant in EHHADH is responsible for Fanconi syndrome with early liver dysfunction and mitochondrial abnormalities - P. Rollier; A. Cospain; M. Barth; V. Milon; N. Gueguen; C. Homedan; V. Desquiret; C. Bris; E. Colin; L. Damaj; A. Ryckewaert; P. Reynier; et al. (Molecular Genetics and Metabolism Reports)
Background: The recurrent pathogenic variant c.7G>A p.Glu3Lys in the EHHADH gene is responsible for an autosomal dominant form of Fanconi renotubular syndrome. This variant leads to mislocalization of peroxisomal EHHADH protein to the mitochondria, thereby impairing mitochondrial function. To date, this variant has been reported in only two unrelated families, with affected individuals presenting with isolated renotubular Fanconi syndrome. No other pathogenic variant has been documented in this gene. Methods: A boy followed from four months-old to twelve years-old underwent clinical evaluation, mitochondrial analyses and exome sequencing. Results: The four-month-old infant boy presented with hypoglycemia, ketonuria, lactic acidosis and hepatic cytolysis. Three months later, a Fanconi tubulopathy with nephrocalcinosis appeared. Mitochondrial respiratory chain analyses performed on hepatocytes showed a decreased activity of complex I and IV of the mitochondrial respiratory chain and a quantitative decrease of these complexes. Exome sequencing revealed the missense variant c.7G>A p.Glu3Lys, inherited from his father who was asymptomatic at 54 years old. A diet supplemented in medium-chain fatty acids was experimented. Conclusion: This case widens the phenotypic spectrum of the recurrent p.Glu3Lys variant in EHHADH, which may be responsible for Fanconi syndrome and early onset hepatic dysfunction with cytolysis and hypoglycemia. Medium-chain fatty acids supplemented diet did not improve the disease.